Mente humana y creación literaria - Carrasco, Iván (Revista Chilena de Humanidades, 2016)
Taking as a starting point the postulate of the universality and permanenceof literature as a human phenomenon, sorne relationship with the mind are es tablished by means of the study of the act of artistic creation, the connections between mind, text and reality, psychological literature, some procedures wich clearly indicate mental processes. and literature as a document to be studied.